Salt stress causes cell wall damage in yeast cells lacking mitochondrial DNA - Qiuqiang Gao; Liang-Chun Liou; Qun Ren; Xiaoming Bao; Zhaojie Zhang (Microbial Cell, 2015)
The yeast cell wall plays an important role in maintaining cell morphology, cell integrity and response to environmental stresses. Here, we report that salt stress causes cell wall damage in yeast cells lacking mitochondrial DNA (ρ0). Upon salt treatment, the cell wall is thickened, broken and becomes more sensitive to the cell wall-perturbing agent sodium dodecyl sulfate (SDS). Also, SCW11 mRNA levels are elevated in ρ0 cells. Deletion of SCW11 significantly decreases the sensitivity of ρ0 cells to SDS after salt treatment, while overexpression of SCW11 results in higher sensitivity. In addition, salt stress in ρ0 cells induces high levels of reactive oxygen species (ROS), which further damages the cell wall, causing cells to become more sensitive towards the cell wall-perturbing agent.